1994
DOI: 10.1063/1.112947
|View full text |Cite
|
Sign up to set email alerts
|

Site-competition epitaxy for superior silicon carbide electronics

Abstract: We present and discuss a novel dopant control technique for compound semiconductors, called site-competition epitaxy, which enables a much wider range of reproducible doping control and affords much higher and lower epilayer doping concentrations than was previously possible. Site-competition epitaxy is presented for the chemical vapor deposition of 6H-SiC epilayers on commercially available (0001)SiC silicon-face substrates. Results from utilizing site-competition epitaxy include the production of degeneratel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
173
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 305 publications
(192 citation statements)
references
References 3 publications
17
173
1
1
Order By: Relevance
“…Even taking into account that the growth rate could influence the incorporation, the result is in line with the site competition theory 9 . For the incorporation of Al, higher doping levels are observed upstream where the effective C/Si ratio is expected to be higher than downstream where the opposite conditions prevail.…”
Section: B P-type Doping Using Tmalsupporting
confidence: 62%
See 1 more Smart Citation
“…Even taking into account that the growth rate could influence the incorporation, the result is in line with the site competition theory 9 . For the incorporation of Al, higher doping levels are observed upstream where the effective C/Si ratio is expected to be higher than downstream where the opposite conditions prevail.…”
Section: B P-type Doping Using Tmalsupporting
confidence: 62%
“…The substitutional incorporation of Al and N in the SiC lattice is controlled by the site-competition theory where Al is thought to replace Si and N is thought to replace C in the SiC lattice. 9 This makes the C/Si ratio in the CVD gas mixture the key parameter for controlling the amount of incorporated dopants. Doping incorporation in a chlorinated chemistry has been studied in detail and it was found that n-type doping by N2 and tertbutylphosphine (TBP: C4H9 PH2) for doping with phosphorus was easily done and not affected by the presence of chlorine, 10 12 where Al doping in the 10 20 cm -3 range was measured by SIMS.…”
Section: Introductionmentioning
confidence: 99%
“…This fact gives the argument to suggest that the absence of the N k1 substituting C site is caused by technology preparation of the np-SiC rather than by compensation eect. Indeed, in accordance with the sitecompetition principle proposed in [8], the C-excess in 6H…”
Section: Methodsmentioning
confidence: 88%
“…8 TMA is a common p type doping source for single-crystal SiC films. 12,13 Cross-section high resolution transmission electron microscopy ͑HRTEM͒ ͑FEI Tecnai F30͒ and capacitancevoltage ͑C-V͒ techniques were employed to characterize the deposited SiC films. To enable C-V measurements, the SiC surface was cleaned and aluminum was thermally evaporated and patterned into 0.001 cm 2 electrodes surrounded by a much larger area electrode acting as a low impedance second contact.…”
mentioning
confidence: 99%